Treatment of Menstrual Diarrhea Based on the “Four Dimensions Regulating the Central Earth” Theory - Wang, Zixing; Xiao, Xinchun; Zhang, Zehui (Journal of Contemporary Medical Practice, 2025)
Menstrual diarrhea is a common disease accompanying the menstrual cycle, which seriously affects patients’ quality of life. Traditionally, it is mostly treated based on the theories of “disharmony between the liver and spleen” or “deficiency of spleen and kidney yang”. Although effective, the underlying mechanism of qi movement remains to be elaborated. The “Four Dimensions Regulating the Central Earth” theory takes the “spleen-earth” as the core and the four zang-organs (liver, heart, lung, kidney) as the four dimensions, systematically explaining how the qi movement of the four zang-organs surrounds the middle earth and coordinately regulates the pivot movement to maintain the normal transportation and distribution of food nutrients. This review systematically sorts out the origin and development of this theory, deeply analyzes its guiding significance in the core pathogenesis of menstrual diarrhea (“deficient earth failing to pivot, four dimensions losing coordination”), and summarizes the relevant clinical treatment principles and prescriptions, aiming to provide new ideas and theoretical basis for the diagnosis and treatment of this disease.